'Not Enough': Killing Time in London's Itchy Park. Issue 2 (15th March 2021) - Burraway, Joshua
ABSTRACT: This article investigates the ways in which psychoactive substances, boredom, temporality, and biopolitical forces intersect to constitute the situation of homeless addiction in inner-city London. It argues that the temporal scales intrinsic to this situation can be conceptualised as an immanent field of sociopolitical, economic, and moral relations that are constituted above all by precarity. Inseparably bound up within these precarious fields are complex constellations of care and economy that place the homeless in a particular relation to each other and, simultaneously, the state. Further, it explores how homeless people use psychoactive substances to negotiate the unbearable 'present-ness' of their situation by displacing their subjectivities into alternative temporal states. In so doing, it interrogates the way that conflicting spatio-temporal scales fold into broader matrices of power, abjection, and governance, specifically exploring the ways in which the people most disadvantaged by this enfolding continue to navigate their way through the turbulence.